Acute abdominal pain in emergency room: Is it always a simple diagnosis? (Emergency Care Journal, 2018)
Acute abdominal pain is characterized by pain arising from the abdominal area, of non-traumatic origin with a maximum duration of five days and represents a true medical emergency. It is also one of the most common reasons for referral to an emergency department and the most common cause for no trauma-related hospital admissions. Hematologic disorders represent the 0.3% of all admissions for acute abdominal pain. We report a rare case of retroperitoneal bulky mass due to anaplastic large T-cell lymphoma. This entity represents a rare tumor and early diagnosis leads to a correct diagnosis of the origin of the acute abdominal pain and chemotherapy is vital to ensure good prognosis.
Keywords: Large T cell lymphoma; abdominal pain; Retroperitoneaum; Non-hodgkin lymphoma